A multi-function travel mobile application Wunder : travel app - Ng, Hao En (Nanyang Technological University, 2021)
Globalization has empowered humans to enjoy many benefits and one of the benefits is lower cost of flights that allow more people to explore different parts of the world. People today look forward to overseas holidays as means of escape from their mundane work life and often an opportunity to spend time with friends and family members. The combination of the rise in technology and growth in the travel industry, lead to the development of many travel applications. With 48.41% of the world population owning a smartphone[1], most travelers will look into travel applications to enhance their trip experience. Travel applications available in the market covers many aspect of traveling, from planning itinerary to booking of accomodations, fights and attactions.Wunder is an itinerary planner that aims to ease the process of planning a trip especially for groups. The main features in Wunder includes live mutliple user itinerary planning, in-app live chat and it utilise the Google Map API for mapping the points on the trip on to a geological view. Wunder is also designed on a framework that allows the application to run on both iOS and Android catering to every users that have access to a smartphone.